Effect of a Sustained Reduction in Plasma Free Fatty Acid Concentration on Intramuscular Long-Chain Fatty Acyl-CoAs and Insulin Action in Type 2 Diabetic Patients - Bajaj, Mandeep; Suraamornkul, Swangjit; Romanelli, Anthony; Cline, Gary W.; Mandarino, Lawrence J.; Shulman, Gerald I.; DeFronzo, Ralph A. (Diabetes (New York, N.Y.), 2005)
Effect of a Sustained Reduction in Plasma Free Fatty Acid Concentration on Intramuscular Long-Chain Fatty Acyl-CoAs and Insulin Action in Type 2 Diabetic Patients Mandeep Bajaj 1 , Swangjit Suraamornkul 1 , Anthony Romanelli 2 , Gary W. Cline 2 , Lawrence J. Mandarino 1 , Gerald I. Shulman 2 and Ralph A. DeFronzo 1 1 Diabetes Division, Department of Medicine, University of Texas Health Science Center, San Antonio, Texas 2 Howard Hughes Medical Institute and the Departments of Internal Medicine and Cellular and Molecular Physiology, Yale University School of Medicine, New Haven, Connecticut Address correspondence and reprint requests to Mandeep Bajaj, MD, Associate Professor, Endocrinology Division, Department of Medicine, University of Texas Medical Branch, 301 University Blvd., Galveston, TX 77555-1060. E-mail: mandeepbajajathotmail.com Abstract To investigate the effect of a sustained (7-day) decrease in plasma free fatty acid (FFA) concentrations on insulin action and intramyocellular long-chain fatty acyl-CoAs (LCFA-CoAs), we studied the effect of acipimox, a potent inhibitor of lipolysis, in seven type 2 diabetic patients (age 53 ± 3 years, BMI 30.2 ± 2.0 kg/m 2 , fasting plasma glucose 8.5 ± 0.8 mmol/l, HbA 1c 7.5 ± 0.4%). Subjects received an oral glucose tolerance test (OGTT) and 120-min euglycemic insulin (80 mU/m 2 per min) clamp with 3-[ 3 H]glucose/vastus lateralis muscle biopsies to quantitate rates of insulin-mediated whole-body glucose disposal ( R d ) and intramyocellular LCFA-CoAs before and after acipimox (250 mg every 6 h for 7 days). Acipimox significantly reduced fasting plasma FFAs (from 563 ± 74 to 230 ± 33 μmol/l; P < 0.01) and mean plasma FFAs during the OGTT (from 409 ± 44 to 184 ± 22 μmol/l; P < 0.01). After acipimox, decreases were seen in fasting plasma insulin (from 78 ± 18 to 42 ± 6 pmol/l; P < 0.05), fasting plasma glucose (from 8.5 ± 0.8 to 7.0 ± 0.5 mmol/l; P < 0.02), and mean plasma glucose during the OGTT (from 14.5 ± 0.8 to 13.0 ± 0.8 mmol/l; P < 0.05). After acipimox, insulin-stimulated R d increased from 3.3 ± 0.4 to 4.4 ± 0.4 mg · kg −1 · min −1 ( P < 0.03), whereas suppression of endogenous glucose production (EGP) was similar and virtually complete during both insulin clamp studies (0.16 ± 0.10 vs. 0.14 ± 0.10 mg · kg −1 · min −1 ; P > 0.05). Basal EGP did not change after acipimox (1.9 ± 0.2 vs. 1.9 ± 0.2 mg · kg −1 · min −1 ). Total muscle LCFA-CoA content decreased after acipimox treatment (from 7.26 ± 0.58 to 5.64 ± 0.79 nmol/g; P < 0.05). Decreases were also seen in muscle palmityl CoA (16:0; from 1.06 ± 0.10 to 0.75 ± 0.11 nmol/g; P < 0.05), palmitoleate CoA (16:1; from 0.48 ± 0.05 to 0.33 ± 0.05 nmol/g; P = 0.07), oleate CoA (18:1; from 2.60 ± 0.11 to 1.95 ± 0.31 nmol/g; P < 0.05), linoleate CoA (18:2; from 1.81 ± 0.26 to 1.38 ± 0.18 nmol/g; P = 0.13), and linolenate CoA (18:3; from 0.27 ± 0.03 to 0.19 ± 0.02 nmol/g; P < 0.03) levels after acipimox treatment. Muscle stearate CoA (18:0) did not decrease after acipimox treatment. The increase in R d correlated strongly with the decrease in muscle palmityl CoA ( r = 0.75, P < 0.05), oleate CoA ( r = 0.76, P < 0.05), and total muscle LCFA-CoA ( r = 0.74, P < 0.05) levels. Plasma adiponectin did not change significantly after acipimox treatment (7.9 ± 1.8 vs. 7.5 ± 1.5 μg/ml). These data demonstrate that the reduction in intramuscular LCFA-CoA content is closely associated with enhanced insulin sensitivity in muscle after a chronic reduction in plasma FFA concentrations in type 2 diabetic patients despite the lack of an effect on plasma adiponectin concentration. EGP, endogenous glucose production FFA, free fatty acid LCFA-CoA, long-chain fatty acyl-CoA OGTT, oral glucose tolerance test Footnotes Accepted August 9, 2005. Received April 6, 2005. DIABETES